Results of the Russian Society of Cardiology survey "Chronic heart failure. Unsolved issues" - O. B. Irtyuga; S. V. Nedogoda; М. Yu. Sitnikova M.Yu.; А. S. Galyavich; S. V. Villevalde; A. O. Nedoshivin; A. O. Konradi; E. V. Shlyakhto (Российский кардиологический журнал, 2024)
Aim. To analyze the readiness of the professional medical community for changes in the classification and implementation of novel approaches to heart failure (HF) treatment based on an online survey.Material and methods. Anonymous online survey of physicians on the official website of the Russian Society of Cardiology (www.scardio.ru) "Chronic heart failure. Unsolved issues" was held from September 30 to October 4, 2023. The survey involved 1015 doctors with an average length of work >10 years, mainly cardiologists (n=810, 83,2%).Results. The majority (n=591, 58,2%) of respondents considered it necessary to identify the HF prestage in the classification, similar to prediabetes or prehypertension, while only 2,2% (n=22) of respondents did not consider it necessary to indicate the HF risk in the classification. Simplifying the HF classification based on the left ventricular ejection fraction (LVEF) values with the identification of only two gradations of LVEF <50% and LVEF ³50% was supported by 60,3% (n=612) of specialists.The majority (80,8%) of respondents supported increasing the time of admission of a patient with HF to 30 minutes to ensure the healthcare quality. According to the survey, only 32% of respondents have the ability to determine the brain natriuretic peptide level in patients with HF without restrictions, which indicates insufficient material security for the implementation of clinical guidelines in practice. Quadruple therapy is prescribed to every patient with HF by only 37% of respondents who took part in the survey, which may indicate clinical inertia regarding following the guidelines.Conclusion. In general, the survey demonstrated high awareness of physicians about the problem of HF and readiness to assess the risk and diagnose HF at preclinical stages, as well as a positive attitude towards changing the classification.